Internationalizing higher education with Thainess: a narrative case study of a rural-based university in Thailand - Matthew R. Ferguson (2022)
Internationalization is a key development strategy for universities in Thailand. This has meant a surge in international program offerings and the establishment of international colleges on many campuses. However, what distinguishes an International Education (IE) in the Thai context is a tricky question. Most often, it is described by what it is not: not Thai. The complex adaptation of IE is rooted in historical narratives of independence, the adoption of western symbols, and the distancing from backward ways of life associated with the Thai countryside. This case study describes a rural-based university that made internationalization central to its organizational identity. The researcher uses narrative inquiry to examine the stories told by the university executive about the organization’s positioning regarding internationalization. The narrative is analyzed against a historical and socio-cultural framework. The results show that Thai culture and the distinct geographical location are integral to the rural-based university’s approach to IE. It is argued that this demonstrates a more inclusive vision of IE in Thai higher education and offers a counter-narrative to Thainess as irreconcilable with internationalization.